Difficulties encountered in the toeic listening test by trade union university’s students - Nguyễn Ngọc Lan (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Among 4 English skills, listening plays an important part, but it is difficult for learners. For TOEIC, listening together with reading is considered  essential skills in international working environment. The paper proposes some difficulties and measures  for drilling listening test for Trade union univeristy’s students.